Die Ermordung von psychisch kranken Menschen in Poltava (1941-1943): Einblicke aus deutschen und sowjetischen Ermittlungsakten und Justizkooperation im Kalten Krieg = The murder of psychiatric patients in Poltava (1941-1943) - Tytarenko, Dmytro; Penter, Tanja (Jahrbücher für Geschichte Osteuropas, 2020)
This article looks at the murder of around 800 psychiatric patients in Poltava, Ukraine under German occupation 1941-1943 by Sonderkommando 4b, local SD units, German and Ukrainian police, in the light of the subsequent legal investigation of the crime by Soviet and East and West German judicial authorities. The article shows that the mass murder was motivated by supply logic of the Wehrmacht and, from the beginning, was coordinated by the Wehrmacht offices responsible and the SS and police apparatus. In contrast to the Reich and occupied Poland, there was no systematic murder of the sick and disabled in the occupied Soviet territories. The subsequent legal investigation of the crime also opened up the prospect of unexpectedly successful German-Soviet judicial cooperation at the height of the Cold War and the confrontation between the two blocs. In today’s German and Ukrainian culture of remembrance of Nazi and war victims,